Preparation method of metal organic framework gel mixed matrix membrane and application of metal organic framework gel mixed matrix membrane in CO2 / CH4 separation

By using MOF gel as filler in the CO2/CH4 separation membrane and building a continuous gas molecular transmission channel in the polyimide matrix through in-situ polymerization, the problems of high energy consumption, high cost and non-selective interface voids in the prior art are solved, and the efficient and low-cost CO2/CH4 separation effect is achieved.

CN119588187AActive Publication Date: 2025-03-11HUNAN UNIV

Patent Information

Application Number
CN202510048716.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-11
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, high cost and possible secondary pollution in CO2/CH4 separation, and the production of mixed matrix membranes is difficult to avoid the generation of non-selective interface voids, which affects membrane performance.

Method used

Metal organic frame (MOF) gel is used as filler to build a continuous gas molecular transmission channel in the polyimide matrix through in-situ polymerization to enhance the interface compatibility between the filler and the matrix and avoid the generation of non-selective interface voids.

Benefits of technology

The permeability flux and separation selectivity of the hybrid matrix membrane are significantly enhanced, the separation efficiency of CO2/CH4 is improved, energy consumption and cost are reduced, and the occurrence of secondary pollution is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588187A_ABST
    Figure CN119588187A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a metal organic framework gel mixed matrix membrane and application of the metal organic framework gel mixed matrix membrane in CO2 / CH4 separation, and belongs to the technical field of gas separation membranes. The method comprises the following steps: dispersing metal organic framework (MOF) gel into a solvent to obtain a solution containing an MOF gel network; then, sequentially adding diamine and dianhydride monomers into the solution, and carrying out polymerization reaction to directly prepare a mixed matrix membrane casting solution; then, uniformly coating a glass culture dish with the membrane casting solution, and finally obtaining the mixed matrix membrane through the steps of heat treatment, cleaning and drying. The method is mild in preparation condition and simple to operate. The MOF gel is selected as a filler, a continuous transmission channel is constructed in a solvent, and in-situ polymerization is performed to form a polyimide matrix, so that the permeation flux of the separation membrane is remarkably improved, and the interfacial compatibility between the filler and the matrix is effectively enhanced. The prepared mixed matrix membrane shows excellent CO2 / CH4 separation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a metal organic framework gel mixed matrix membrane and application thereof in CO2 / CH4 separation, and specifically belongs to the technical field of gas separation membranes. Background Art

[0002] Under the guidance of the "dual carbon" goal, the energy revolution is gradually advancing, aiming to reduce the proportion of mainstream carbon-emitting energy such as coal and oil in consumer energy and develop high-quality renewable energy. As a clean and renewable energy source, biogas shows good application prospects in power generation, heating, natural gas substitution and other fields. However, the large amount of CO2 in biogas not only reduces its calorific value, but may also cause corrosion of transportation and storage equipment. Therefore, efficient separation of CO2 and CH4 is of great significance for improving biogas quality, reducing greenhouse gas emissions and promoting the development of carbon capture and storage technology.

[0003] Although traditional separation methods such as cryogenic distillation and chemical absorption can achieve efficient separation, they have problems such as high energy consumption, high cost and possible secondary pollution. In recent years, membrane separation technology has shown great potential in the field of CO2 / CH4 separation due to its advantages such as low energy consumption, simple operation and easy scale-up. Mixed matrix membranes (MMMs), as a research hotspot in the field of gas separation membranes, combine the excellent separation performance of inorganic membranes with the advantages of easy processing and manufacturing of polymer materials, showing excellent permeability, selectivity and mechanical strength. However, the manufacture of defect-free MMMs is still challenging, because the lack of compatibility between fillers and polymers often leads to the generation of non-selective interfacial voids, which adversely affects membrane performance.

[0004] Therefore, the present invention designs a mixed matrix membrane with metal organic framework (MOF) gel as filler and in-situ polymerization to form a polymer matrix. The MOF gel is dispersed in a solvent to construct a continuous transmission channel; then diamine and dianhydride monomers are added in sequence, and in-situ polymerization is formed around the gel network to form a polyimide matrix, thereby enhancing the interface compatibility between the filler and the matrix, effectively avoiding the generation of non-selective interface voids, and obtaining a high-performance mixed matrix membrane. Summary of the invention

[0005] The purpose of the present invention is to provide a simple and reliable preparation method for preparing mixed matrix membranes (MMMs) capable of efficiently separating CO2 / CH4. The MMMs use MOF gel as filler and polyimide as polymer matrix; the gel network constructs a continuous and effective transmission channel for gas molecules, and the in-situ polymerization preparation method ensures good interface compatibility between the filler and the matrix, thereby giving the MMMs high separation performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A MOF gel mixed matrix membrane used for CO2 / CH4 separation is prepared by an in-situ polymerization method using MOF gel as a filler and polyimide as a polymer matrix.

[0008] The in-situ polymerization method refers to: dispersing the MOF gel in a solvent, then dissolving the diamine and dianhydride monomers in the solvent system in turn, allowing these monomers to undergo in-situ polymerization around the MOF gel network to form a polyimide matrix, and directly preparing a mixed matrix casting solution.

[0009] A method for preparing a MOF gel mixed matrix membrane for CO2 / CH4 separation comprises the following steps:

[0010] S1: Disperse a certain mass of metal organic framework (MOF) gel into the solvent and stir evenly;

[0011] S2: dissolving a certain amount of diamine monomer into the solution obtained in S1, and then adding a certain amount of dianhydride monomer, and reacting for several hours;

[0012] S3: adding a certain amount of catalyst and dehydrating agent to carry out imidization reaction to obtain a mixed matrix casting solution;

[0013] S4: Take a certain amount of casting liquid and evenly apply it on a glass culture dish, and place it in an oven for heat treatment;

[0014] S5: Peeling off the heat-treated film from the culture dish, immersing it in a methanol solution, and obtaining a UiO-66 gel mixed matrix membrane after sufficient drying.

[0015] In the step S1, the MOF gel is UiO-66 gel with a mass of 0.05 g to 0.12 g; the solvent is N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, preferably N,N-dimethylformamide (DMF); and the solvent volume is 11 mL.

[0016] In step S2, the diamine monomer is 4,4'-diaminodiphenyl ether (ODA), with a mass of 0.4 g; the dianhydride monomer is 4,4'-(hexafluoroisopropylene) diphthalic anhydride (6FDA), with a mass of 0.91 g. The reaction device is a three-necked flask, the reaction is carried out under an argon or nitrogen atmosphere, the reaction temperature is 0°C, and the reaction time is 6-12 hours.

[0017] In step S3, the catalyst is triethylamine, and the amount used is 0.27-1.2 mL; the dehydrating agent is acetic anhydride, and the amount used is 0.71-3.2 mL; the imidization reaction temperature is room temperature, and the reaction time is 12-24 h.

[0018] In step S4, the mass of the casting liquid is 0.5-1.5 g, the inner diameter of the glass culture dish is 5 cm, and the heat treatment temperature is 120-220°C.

[0019] In step S5, the soaking time is 24-48 hours; the drying condition is 120° C. under vacuum for 24 hours.

[0020] The above-mentioned MOF gel mixed matrix membrane is used for CO2 / CH4 separation.

[0021] The beneficial effects of the present invention are: 1) MOF gel is evenly dispersed in the polymer matrix to construct a continuous and effective gas molecule transmission channel, which significantly enhances the permeation flux of MMMs; 2) The abundant metal sites and organic linkers in the MOF gel can attract diamine and dianhydride monomers through coordination and hydrogen bonding, causing them to undergo polymerization reactions around the gel network, thereby enhancing the compatibility between the filler and the polymer and avoiding the generation of non-selective interface voids. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) is a scanning electron microscope plan view of the polyimide film in Comparative Example 2; Figure 1 (b) is a scanning electron microscope cross-sectional image of the polyimide film in Comparative Example 2.

[0023] Figure 2 (a) is a scanning electron microscopy plan view of the mixed matrix membrane in Example 3; Figure 2 (b) is a scanning electron microscope cross-sectional image of the mixed matrix membrane in Example 3.

[0024] Figure 3 FTIR spectra of the mixed matrix membrane in Example 3 and the polyimide membrane in Comparative Example 2.

[0025] Figure 4 These are the long-term performance test results of the mixed matrix membrane prepared in Example 2. DETAILED DESCRIPTION

[0026] Example 1

[0027] (1) Preparation of MOF gel. 0.2332 g ZrCl4 and 0.1661 g terephthalic acid were mixed and placed in natural air for 12 h, then completely dissolved in 40 mL DMF by ultrasound, and then 5 mL glacial acetic acid was added and ultrasound was performed for 5 min; then the solution was placed in a 100 mL reactor and reacted at 120 °C for 24 h to obtain a solidified UiO-66 gel, which was fully centrifuged, cleaned, and activated before use; the cleaning and activation reagents were both DMF.

[0028] (2) Disperse 0.05 g of UiO-66 gel in 11 mL of DMF and stir evenly.

[0029] (3) The above UiO-66 gel solution was transferred to a three-necked flask, and an ice-water bath was used under an argon atmosphere with a stirring speed of 600 rpm. 0.4 g of ODA was first added and stirred for 0.5 h. Then 0.91 g of 6FDA was added and stirred for 6 h.

[0030] (4) At room temperature, add 1.2 mL of triethylamine and 3.2 mL of acetic anhydride and continue stirring for 12 h to obtain a mixed matrix casting solution.

[0031] (5) Take 1.0 g of the mixed matrix casting solution and evenly apply it on the bottom of a glass culture dish with an inner diameter of 5 cm, and place it in an oven at 120°C for 12 h.

[0032] (6) The heat-treated film was peeled off from the culture dish and immersed in a methanol solution for 24 hours; the film was then placed in a vacuum oven and dried at 120° C. for 24 hours to obtain the final mixed matrix membrane.

[0033] The mixed matrix membrane prepared in this example was subjected to a CO2 / CH4 mixed gas permeation test, wherein the volume ratio of CO2 to CH4 was 1:1, the inlet pressure was 1 bar, and the test temperature was 35° C. The test results showed that the permeability coefficient of CO2 was 15.06 Barrer, and the separation selectivity of CO2 / CH4 was 69.53.

[0034] Comparative Example 1

[0035] (1) 11 mL of DMF was placed in a three-necked flask and stirred at 600 rpm in an ice-water bath under an argon atmosphere. 0.4 g of ODA was first added and stirred for 0.5 h. Then, 0.91 g of 6FDA was added and stirred for 6 h.

[0036] (2) At room temperature, add 1.2 mL of triethylamine and 3.2 mL of acetic anhydride and continue stirring for 12 h to obtain a polyimide casting solution.

[0037] (3) Take 1.0 g of polyimide casting solution and evenly apply it on the bottom of a glass culture dish with an inner diameter of 5 cm, and place it in an oven at 120°C for 12 h.

[0038] (4) The heat-treated film was peeled off from the culture dish and immersed in a methanol solution for 24 hours; the film was then placed in a vacuum oven and dried at 120° C. for 24 hours to obtain a final polyimide film.

[0039] The polyimide membrane prepared in this embodiment was subjected to a CO2 / CH4 mixed gas permeation test, wherein the volume ratio of CO2 to CH4 was 1:1, the inlet pressure was 1 bar, and the test temperature was 35° C. The test results showed that the permeability coefficient of CO2 was 7.13 Barrer, and the separation selectivity of CO2 / CH4 was 22.44.

[0040] Example 2

[0041] (1) Preparation of MOF gel. Same as Example 1.

[0042] (2) Disperse 0.05 g of UiO-66 gel in 11 mL of DMF and stir evenly.

[0043] (3) The above UiO-66 gel solution was transferred to a three-necked flask, and an ice-water bath was used under an argon atmosphere with a stirring speed of 600 rpm. 0.4 g of ODA was first added and stirred for 0.5 h. Then 0.91 g of 6FDA was added and the stirring was continued for 12 h.

[0044] (4) At room temperature, 0.27 mL of triethylamine and 0.72 mL of acetic anhydride were added and stirred for 12 h to obtain a mixed matrix casting solution.

[0045] (5) Take 1.0 g of the mixed matrix casting solution and evenly apply it on the bottom of a glass culture dish with an inner diameter of 5 cm, and place it in an oven at 120°C for 12 h.

[0046] (6) The heat-treated film was peeled off from the culture dish and immersed in a methanol solution for 24 hours; the film was then placed in a vacuum oven and dried at 120° C. for 24 hours to obtain the final mixed matrix membrane.

[0047] The mixed matrix membrane prepared in this example was subjected to a CO2 / CH4 mixed gas permeation test, wherein the volume ratio of CO2 to CH4 was 1:1, the inlet pressure was 1 bar, and the test temperature was 35° C. The test results showed that the permeability coefficient of CO2 was 29.64 Barrer, and the separation selectivity of CO2 / CH4 was 81.97.

[0048] Example 3

[0049] (1) Preparation of MOF gel. Same as Example 1.

[0050] (2) Disperse 0.075 g of UiO-66 gel in 11 mL of DMF and stir evenly.

[0051] (3) The above UiO-66 gel solution was transferred to a three-necked flask, and an ice-water bath was used under an argon atmosphere with a stirring speed of 600 rpm. 0.4 g of ODA was first added and stirred for 0.5 h. Then 0.91 g of 6FDA was added and the stirring was continued for 12 h.

[0052] (4) At room temperature, 0.27 mL of triethylamine and 0.72 mL of acetic anhydride were added and stirred for 12 h to obtain a mixed matrix casting solution.

[0053] (5) Take 1.0 g of the mixed matrix casting solution and evenly apply it on the bottom of a glass culture dish with an inner diameter of 5 cm, and place it in an oven at 120°C for 12 h.

[0054] (6) The heat-treated film was peeled off from the culture dish and immersed in a methanol solution for 24 hours; the film was then placed in a vacuum oven and dried at 120° C. for 24 hours to obtain the final mixed matrix membrane.

[0055] The mixed matrix membrane prepared in this example was subjected to a CO2 / CH4 mixed gas permeation test, wherein the volume ratio of CO2 to CH4 was 1:1, the inlet pressure was 1 bar, and the test temperature was 35° C. The test results showed that the permeability coefficient of CO2 was 30.90 Barrer, and the separation selectivity of CO2 / CH4 was 135.54.

[0056] Example 4

[0057] (1) Preparation of MOF gel. Same as Example 1.

[0058] (2) Disperse 0.10 g of UiO-66 gel in 11 mL of DMF and stir evenly.

[0059] (3) The above UiO-66 gel solution was transferred to a three-necked flask, and an ice-water bath was used under an argon atmosphere with a stirring speed of 600 rpm. 0.4 g of ODA was first added and stirred for 0.5 h. Then 0.91 g of 6FDA was added and the stirring was continued for 12 h.

[0060] (4) At room temperature, 0.27 mL of triethylamine and 0.72 mL of acetic anhydride were added and stirred for 12 h to obtain a mixed matrix casting solution.

[0061] (5) Take 1.0 g of the mixed matrix casting solution and evenly apply it on the bottom of a glass culture dish with an inner diameter of 5 cm, and place it in an oven at 120°C for 12 h.

[0062] (6) The heat-treated film was peeled off from the culture dish and immersed in a methanol solution for 24 hours; the film was then placed in a vacuum oven and dried at 120° C. for 24 hours to obtain the final mixed matrix membrane.

[0063] The mixed matrix membrane prepared in this example was subjected to a CO2 / CH4 mixed gas permeation test, wherein the volume ratio of CO2 to CH4 was 1:1, the inlet pressure was 1 bar, and the test temperature was 35° C. The test results showed that the permeability coefficient of CO2 was 21.17 Barrer, and the separation selectivity of CO2 / CH4 was 90.69.

[0064] Comparative Example 2

[0065] (1) 11 mL of DMF was placed in a three-necked flask and stirred at 600 rpm in an ice-water bath under an argon atmosphere. 0.4 g of ODA was first added and stirred for 0.5 h. Then 0.91 g of 6FDA was added and stirred for 12 h.

[0066] (2) At room temperature, 0.27 mL of triethylamine and 0.72 mL of acetic anhydride were added and stirred for 12 h to obtain a polyimide casting solution.

[0067] (3) Take 1.0 g of polyimide casting solution and evenly apply it on the bottom of a glass culture dish with an inner diameter of 5 cm, and place it in an oven at 120°C for 12 h.

[0068] (4) The heat-treated film was peeled off from the culture dish and immersed in a methanol solution for 24 hours; the film was then placed in a vacuum oven and dried at 120° C. for 24 hours to obtain a final polyimide film.

[0069] The polyimide membrane prepared in this embodiment was subjected to a CO2 / CH4 mixed gas permeation test, wherein the volume ratio of CO2 to CH4 was 1:1, the inlet pressure was 1 bar, and the test temperature was 35° C. The test results showed that the permeability coefficient of CO2 was 9.90 Barrer, and the separation selectivity of CO2 / CH4 was 51.85.

[0070] Figure 1 (a) is a scanning electron microscope plan view of the polyimide film in Comparative Example 2; Figure 1 (b) is a cross-sectional view of the polyimide film in Comparative Example 2. Figure 1 It can be seen from (a) and (b) that the polyimide film prepared in Comparative Example 2 has a smooth surface and no defects, and the internal matrix is ​​evenly distributed and continuous.

[0071] Figure 2 (a) is a scanning electron microscopy plan view of the mixed matrix membrane in Example 3; Figure 2 (b) is a cross-sectional view of the mixed matrix membrane in Example 3. Figure 2 As can be seen from (a) and (b), the surface of the polyimide film prepared in Example 3 is smooth, and the UiO-66 gel is evenly and continuously distributed on the surface and inside, without agglomeration and defects, indicating that the UiO-66 gel has good compatibility with the polyimide matrix.

[0072] Figure 3 FTIR spectra of the mixed matrix membrane in Example 3 and the polyimide membrane in Comparative Example 2. In the spectra of Example 3 and Comparative Example 2, 1784 cm -1 (-C=O, asymmetric stretching vibration), 1720cm -1 (-C=O, symmetrical stretching vibration) and 1373cm -1 The characteristic peak at (-CN, stretching vibration) proves that polyimide is successfully prepared, 1236cm -1 (=COC=, stretching vibration) and 1498cm -1 The absorption band at (C=C) is attributed to the vibration of the ODA unit in the polyimide (6FDA-ODA).

[0073] Figure 4 The long-term performance test results of the mixed matrix membrane prepared in Example 2. Figure 4 It can be seen that the permeation performance and separation performance of the prepared mixed matrix membrane are stable for a long time.

[0074] The above embodiments are only intended to illustrate the implementation methods of the present invention and to reveal certain characteristics of its methods and applications, and should not be regarded as limiting the scope of patent protection of the present invention. It should be clear that various changes and adjustments can be made to the basic concept of the present invention without violating it, and all such changes and adjustments fall within the scope of protection of the present invention.

Claims

1. A method for preparing a metal organic framework gel mixed matrix membrane, characterized in that: The following steps are involved: S1: Disperse a certain mass of metal organic framework (MOF) gel into the solvent and stir evenly; S2: dissolving a certain amount of diamine monomer into the solution obtained in S1, and then adding a certain amount of dianhydride monomer, and reacting for several hours; S3: adding a certain amount of catalyst and dehydrating agent to carry out imidization reaction to obtain a mixed matrix casting solution; S4: Take a certain amount of casting liquid and evenly apply it on a glass culture dish, and place it in an oven for heat treatment; S5: Peeling off the heat-treated film from the culture dish, soaking it in a methanol solution, and obtaining a UiO-66 gel mixed matrix membrane after being fully dried.

2. The preparation method according to claim 1, characterized in that In the step S1, the MOF gel is UiO-66 gel with a mass of 0.01 g to 0.12 g; the solvent is N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, preferably N,N-dimethylformamide; and the volume of the solvent is 11 mL.

3. The preparation method according to claim 1, characterized in that: In step S2, the diamine monomer is 4,4'-diaminodiphenyl ether, with a mass of 0.4 g; the dianhydride monomer is 4,4'-(hexafluoroisopropylene) diphthalic anhydride, with a mass of 0.91 g; the reaction apparatus is a three-necked flask, the reaction is carried out under an argon or nitrogen atmosphere, the reaction temperature is 0°C, and the reaction time is 6-12 hours.

4. The preparation method according to claim 1, characterized in that: In step S3, the catalyst is triethylamine, and the amount used is 0.27-1.2 mL; the dehydrating agent is acetic anhydride, and the amount used is 0.72-3.2 mL; the imidization reaction temperature is room temperature, and the reaction time is 12-24 h.

5. The preparation method according to claim 1, characterized in that: In step S4, the mass of the casting liquid is 0.5-1.5 g, the inner diameter of the glass culture dish is 5 cm, and the heat treatment temperature is 120-220°C.

6. The preparation method according to claim 1, characterized in that: In step S5, the soaking time is 24-48 hours; the drying condition is 120° C. under vacuum for 24 hours.

7. A method for preparing a metal organic framework gel mixed matrix membrane, characterized in that: It is prepared by the preparation method of claims 1-7 and used for CO2 / CH4 separation.

Citation Information

Patent Citations

  • Preparation method of UiO-66-NH2-based mixed matrix membrane

    CN115945082A

  • Preparation method and application of gel mixed matrix membrane based on in-situ MOF

    CN119281124A

  • Electronic device and operation method of electronic device for arranging object according to space in augmented reality(AR)

    KR1020240019671A

Cited By

  • Hollow fiber composite matrix membrane

    CN119926210A

  • Carbon dioxide separation membrane as well as preparation method and application thereof

    CN121648762A